Alaskan travels : far-flung tales of love and adventure - Hoagland, Edward (Arcade Pub., 2012)
"Thirty years ago, American writer Edward Hoagland, set out to explore and write about one of the last truly wild territories remaining on the face of the earth: Alaska. From the Arctic Ocean to the Kenai Peninsula, the backstreet bars of Anchorage to the Yukon River, Hoagland traveled the "real" Alaska from top to bottom. Here he documents not only the flora and fauna of America's last frontier, but also the extraordinary people living on the fringe"--P. [4] of cover.